Wear Property of Machined Ultra High Molecular Weight Polyethylene (UHMWPE) Acetabular Liner Product with CNC Milling - Lestari, Wahyu Dwi; Danaryanto, A T; Nugroho, A; Ismail, R; Jamari, J; Bayuseno, A P (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
UHMWPE has been used as a cushion in artificial hip joint for the last decades. The reliability of the components of a hip joint implant can be achieved by understanding their wear behavior. This study observed the tribological performance of the UHMWPE acetabular liner manufactured with a CNC milling machine on the femoral head made of SS 316L. Materials commonly used for tribo pairs in hip joint replacement. The wear tests were performed on a hip joint simulator in dry condition. The wear test is carried out by applying a constant load of 800N. Before and after the wear test, measurements of surface roughness and dimensional accuracy were carried out on the UHMWPE acetabular liner specimen. The correlation between the surface roughness of the machining process and the wear rate is seen from the value of the wear depth and the wear coefficient obtained. The results showed that the machining process affects the surface roughness of the acetabular liner, where the roughness also affects the wear rate of acetabular liner product.